Teaching innovation for the sustainable development (Revista Multi-Ensayos, 2019)
Based on the theory stated by distinguished authors about innovation, this essay main purpose is to emphasize the importance of promoting from the education the learning of innovation for sustainable development. In addition, the experience of innovation promoted in Nicaragua through the universities part of the National Council of Universities (CNU), specifically at the Bluefields Indian and Caribbean University (BICU) is demonstrated. BICU is a communal university, in the Caribbean Coast of Nicaragua, it is recognized by its Cosmo vision, interculturality, and multiculturalism. At the BICU, the experience of entrepreneurship has been promoted with students of the Bachelor of Business Administration, Public Accounting and Finance and Ports and Airports Administration, focused in a combination of theory-practice through the subjects: business vision and formulation and evaluation of Projects. At the BICU, under graduated and graduated students have the opportunity to generate small, medium and large businesses, increasing the local and national market.
Keywords: teaching; innovation; development